الضوابط النقلية لفهم سور القرآن الكريم = Agreed rules for understanding the Holy Quran - Mohammad Alansari, Abdulla; Jamal Yousef, Radwan; Mohamed Shousha, Hossam Moussa (IIUM Press, International Islamic University Malaysia, 2020)
يهدف هذا البحث إلى الكشف عن الضوابط النقلية المعينة على معرفة مقصد السور القرآنية ذات الموضوعات المتعددة والتي ظاهرها التعارض، ويوضح البحث الضوابط النقلية التي يمكن أن تكون منهجا يمكن الاعتماد عليه في التفسير الموضوعي. كما حاول البحث تطبيق هذه القواعد على ثلاث سور من القرآن الكريم وهي الأنعام ويونس والأحزاب. واستخدم البحث المنهج الاستقرائي بتتبع كل ما يتعلق بالتفسير الموضوعي للسورة في كتب التفسير بمختلف مناهجها، والأحاديث النبوية، والآثار ذات الصلة بالموضوع، وكذلك كتب التفسير بالرأي على أنواعها؛ كما استخدم المنهج التحليلي وذلك بدراسة الظاهرة ونقد الأطروحات غير الواضحة مع استنباط ضوابط منهجية معينة على فهم السور القرآنية. وقد توصل البحث إلى عدد من النتائج، من أهمها أن السورة القرآنية لها وحدة موضوعية ومقصد رئيس تنتظم تحته القصص والأمثال والأحكام الشرعية الواردة في السورة. كما توصل البحث إلى ضرورة الاستفادة من المخزون العلمي الذي تركه المفسرون وتوظيف ذلك في خدمة البحث الموضوعي عن مقصد السور القرآنية. كم أثبت البحث أن الاعتناء بالكتابة في ضوابط التفسير الموضوعي وتكوين مرجعية للباحثين في مقاصد السور له من الأهمية ما للضوابط الفقهية والأصولية التي سبقت الضوابط التفسيرية وتم تأصيلها وتأطيرها بشكل واضح، ذكل أن كتابة تفاسير تقوم على أساس مقصدي محدد بضوابط منهجية للسور القرآنية يكون له أبلغ الأثر على من يرغب في فهمها من خلال الوقوف على الترابط المحكم فيها. ******************************************************************************* This research aims to reveal the specific controls on knowing the purpose of the Qur'anic surahs with multiple topics, which are apparent contradictions. On the other hand, the research applied the rules laid down on three chapters of the Holy Qur’an, which are Al Anam, Younis, and Al Ahzab. The research used the inductive method to track everything related to the objective interpretation of the Surah in the books of interpretation in its various curricula, the hadiths of the Prophet, and the effects related to the topic, as well as books of interpretation of opinion on various types; also the analytical method was used by studying the phenomenon and criticizing unclear theses with devising certain methodological controls on understanding the Quranic Surahs. The research also reached a number of results, the most important of which is that the Qur'an surah has an objective unity and a main purpose under which the stories, proverbs and legal rulings mentioned in the surah are organized. The research also reached the necessity of making use of the scientific repository left by the interpreters and employing this in the service of objective research on the purpose of the Qur'anic surahs. How much research proved that caring for writing in the controls of objective interpretation and forming a reference for researchers in the purposes of the fence has important importance for the doctrinal and fundamentalist controls that preceded the explanatory controls and were clearly rooted and framed, as writing interpretations based on a specific purpose with systematic controls of the Quranic fence has the most impact. It is upon those who wish to understand it by identifying the tight linkages therein.